Apparenza del diritto e rapporti di fatto nell'esperienza giuridica di Roma antica - Rossi, Francesca (Premio Tesi di Dottorato, 2020)
The thesis examines the dialectic between fact and law in the juridical experience of Rome in the light of the principle of appearance of law. For each of the main manifestations of the principle of appearance (apparent heir, apparent creditor, apparent representative) a possible historical antecedent in Roman law (possessor pro herede, falsus creditor, falsus procurator) is identified, a detailed analysis of which is proposed, taking into account ancient sources and doctrinal interpretations. Subsequently the 'de facto' family relationships (more uxorio relations, matrimonium iniustum and concubinage) are examined, since they can in turn be traced back to the principle of appearance. In its questioning of the reasons of the extension of the juridical discipline to the apparent case, the research identifies a common tendency to the various phenomena that, although heterogeneous, express the same tension between fact and law present in the legal systems of every historical epoch.